(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The implementation of a switching capacitor filter presents an innovative approach to address the pressing need for advanced filtering solutions in modern electronic systems. This research focuses on the utilization of cutting-edge 90nm technology to create a versatile switching capacitor circuit capable of precise and adaptable signal processing. In this work, the design, simulation, and experimental validation of the filtering circuit is presented in novel approach. The circuit leverages the benefits of 90nm technology, which enables the integration of complex signal processing functions within a compact and power-efficient framework. The utilization of switching capacitor techniques enhances the circuit’s flexibility, allowing it to adapt to a wide range of filtering requirements. The research explores the theoretical foundations of switching capacitor circuits, emphasizing their efficiency and suitability for various applications. Furthermore, we provide in-depth insights into the design principles, component selection, and circuit topology for achieving optimal filtering performance. By employing advanced 90nm technology, we achieve high levels of integration while maintaining low power consumption, making the circuit particularly suitable for portable and battery-powered devices. Simulations and experimental results corroborate the circuit’s effectiveness in practical scenarios. The research presents comprehensive analyses of the circuit’s filtering characteristics, including its frequency response, bandwidth, and signal-to-noise ratio. Additionally, the adaptability of the circuit to different filtering requirements is demonstrated, highlighting its versatility and potential for a wide range of applications.